The Effect of Zig-Zag Running Training using Weights on Increasing Dribbling Ability in Football Athletes Club Porma FC U-20th Kepahiang - Feby Elra Perdima; Remon Pebriadi; Nugraha Adita; Rayvin Domingo Pestano; Wiwik Yunitaningrum (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2023)
The aim of the study was to determine the effect of zig-zag running training using weights on increasing the dribbling ability of the U-20 year old Kepahiang football club Porma Fc athletes. This study used an experimental method with the One Group Pretest – Posttest design. The research instrument used was the Arsil dribbling test with a validity of 0.71 and a reliability of 0.63. The sample in this study consisted of 30 U-20 year old Kepahiang Porma Fc players. The results of the research on the dribbling test were that the pretest average was 51.23, and the posttest average was 57.7, an increase of 12.62%. The results of the t-test analysis between the pre-test and post-test have a significant effect. The calculation results state that the value of t count = 9.95 ≥ t table = 1.669 with a level of α = 0.05. There is a significant effect of zig-zag running training using weights on increasing the dribbling ability of U-20 year old Porma FC Kepahiang players.